Moderation of Foreign Exchange Rates on The Effect of Cryptocurrency and Money Supply on The Indonesia Composite Index (IHSG) - Prastyatini, Sri Lestari Yuli; Tiarah, Ahmad Reski (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to test whether cryptocurrency and money supply affect Indonesia Composite Index (IHSG) with exchange rates as a moderating variable. This research is quantitative research. The population of this study is return value of cryptocurrency, money supply, exchange rates, and Indonesia Composite Index every month during period 2020-2022. The number of samples obtained was 36 data, the data was obtained using saturation sampling technique. This research was conducted using SPSS 26 to test the data. The results of this study state that cryptocurrency have a positive effect on Indonesia Composite Index while money supply have no effect on Indonesia Composite Index. Exchange rates unable to moderate the relationship between cryptocurrency and Indonesia Composite Index but able to moderate the relationship between money supply and Indonesia Composite Index. Mutually, cryptocurrency and money supply jointly affect Indonesia Composite Index by 24,3%. However, this study also highlights the need for further research to look at other factors that can influence the IHSG and its impact on the IHSG.